The LIBER Security Network of 2002 – The Copenhagen Principles - LIBER Quarterly (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
The last decade has seen the rapid development of a number of factors affecting the security of significant library collections. • The market value of large parts of library collections now equals the prices of the most expensive antiques and works of art; • The interest of the free market in items held in libraries is constantly increasing; • Valuable parts of library collections have been subject to grave instances of theft of a trans-national character across Europe. Recognizing these developments, we have decided to set up closer co-operation among libraries with the purpose of preventing or resolving such incidents.